2017
DOI: 10.2147/ott.s125185
|View full text |Cite
|
Sign up to set email alerts
|

A new tumor suppressor lncRNA RP11-190D6.2 inhibits the proliferation, migration, and invasion of epithelial ovarian cancer cells

Abstract: At present, a large number of long noncoding RNAs (lncRNAs) from the human genome have been discovered. Meanwhile, emerging evidence has indicated that lncRNAs could play a critical role in the regulation of cellular processes such as cancer progression and metastasis. However, the functions of some new lncRNAs in the complex transcriptional process are mostly unknown at present. Existing studies suggest that loss of WW domain-containing oxidoreductase (WWOX) expression is linked with poor prognosis in numerou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…For example, Cho et al reported that lncRNA-MALAT1 was overexpressed in patients with multiple myeloma and may serve as a molecular predictor of early progression [14]. Moreover, LncRNAs could function as oncogenes or tumor suppressors in different types of tumors depending on the circumstance [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Cho et al reported that lncRNA-MALAT1 was overexpressed in patients with multiple myeloma and may serve as a molecular predictor of early progression [14]. Moreover, LncRNAs could function as oncogenes or tumor suppressors in different types of tumors depending on the circumstance [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…showed that a lncRNA named RP11-190D6.2 regulates the WW domain-containing oxidoreductase (WWOX) expression by acting like an antisense transcript of this gene [55]. WWOX is linked with poor prognosis in several cancers, including EOC [56].…”
Section: Circulating Long Non-coding Rnasmentioning
confidence: 99%
“…WWOX is linked with poor prognosis in several cancers, including EOC [56]. In addition, RP11-190D6.2 appears to play a role in the regulation of tumor metastasis, thus it can be counted as a potential biomarker and therapeutic target for EOC [55]. Zhou et al compared several lncRNA expression profiles in a large number of OvCa patients from TCGA and found an eight-lncRNA signature predictive of overall survival [57].…”
Section: Circulating Long Non-coding Rnasmentioning
confidence: 99%
“…In recent years, lncRNAs have begun to receive substantial attention in the molecular biology field. Increasing evidence indicates that lncRNAs, as an versatile molecules that interact with RNA, DNA, or proteins to promote or restrain the expression of protein-coding genes, are involved in diverse biological processes, including cell proliferation, differentiation, apoptosis, and development[ 3 5 ]. Moreover, in the field of immunology, various studies have indicated that lncRNAs not only are emerging as important regulators of inflammatory gene expression in innate immune system[ 6 , 7 ], but also play a crucial role in directing the development and apoptosis of diverse immune cells and controlling the dynamic transcriptional programs that are hallmarks of immune cells activation or differentiation in adaptive immune system[ 8 11 ].…”
Section: Introductionmentioning
confidence: 99%